2020
DOI: 10.1002/ccd.29321
|View full text |Cite
|
Sign up to set email alerts
|

A novel fiber‐optic based 0.014″ pressure wire: Designs of the OptoWire™, development phases, and the O2 first‐in‐man results

Abstract: Objectives: To review the technical limitations of available pressure-wires, present the design evolution of a nitinol fiber-optic pressure wire and to summarize the Firstin-Man (FIM) O 2 pilot study results.Background: Despite increasing use of physiology assessment of coronary lesions, several technical limitations persist. We present technical details, design evolution and early clinical results with a novel 0.014" nitinol fiber-optic based pressure-wire.Methods and Results: The 0.014' OptoWire™ (Opsens Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Fiber-optic-based pressure sensors have not only anti-interference ability, high precision, flexibility, and ease of bending, but are also corrosion-resistant, which well meets the above needs. As it becomes an alternative to electro-mechanical pressure sensors, the optical fiber pressure sensor has become increasingly common in the medical field [ 28 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Sensor Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber-optic-based pressure sensors have not only anti-interference ability, high precision, flexibility, and ease of bending, but are also corrosion-resistant, which well meets the above needs. As it becomes an alternative to electro-mechanical pressure sensors, the optical fiber pressure sensor has become increasingly common in the medical field [ 28 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Sensor Applicationsmentioning
confidence: 99%
“…Omori et al [ 86 ] investigated FFR measurement, as shown in Figure 9 . In 2020, Ulacia et al [ 87 ] finished the First-in-Man O 2 pilot study.…”
Section: Sensor Applicationsmentioning
confidence: 99%
“…Therefore, the NAVVUS RXi ® and the TruePhysio™ are microcatheters to be used with any workhorse wire to overcome these issues, with debatable opinions. In vitro assessment of the novel 0.014’’ OptoWire™ showed improved pushability, steerability and torquability in comparison with regular PCI wires, offering reliable pre and post PCI hemodynamic assessment[ 35 ].…”
Section: Fractional Flow Reservementioning
confidence: 99%
“…Shape memory effects have been observed during austenite to martensite transformation, i.e., transformation from the face-centered cubic (FCC) structure to a body-centered tetragonal (BCT) structure (Parmar et al, 2021). Nitinol has gained popularity in the biomedical field, given its corrosion resistance, acceptable biocompatibility, super-elasticity, osseointegration, and fatigue and kink resistance properties (Hamann et al, 2020;Ulacia et al, 2020). The alloy has applications in the biomedical field as coronary stents, dental archwires, and actuators, although the concerns of nickel leaching limit the application (Fouladian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of biomedical applications, it is important to prepare stable monodispersed solutions with NPs possessing less aggregation propensity (Phan and Haes, 2019). The exposure of NPs in a physiological environment leads to absorption of biological substances (proteins, lipids, peptides, nucleic acids, metabolites, and others) onto the surface of the NPs, leading to the formation of biocorona (Shannahan, 2017;Ulacia et al, 2020). The biocorona presents a unique challenge for the practical and safe biomedical application by affecting the toxicity, functionality, and characteristics of NPs and thereby altering thrombogenic properties as well (Chakraborty et al, 2019;Sena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%